2017
DOI: 10.1007/s10067-017-3940-y
|View full text |Cite
|
Sign up to set email alerts
|

Population-based study suggests an increased risk of Alzheimer’sdisease in Sjögren’s syndrome

Abstract: This population-based study was designed to estimate and compare the risk of Alzheimer’s disease (AD) between patients with primary Sjögren’s syndrome (SS) and non-SS patients during a 10-year follow-up period. This is a retrospective cohort study. Data were obtained from the Taiwan’s National Health Insurance Research Database. We identified 4463 primary SS patients and 22,315 non-SS patients; patients were matched by sex, age, and the year of index use of health care. Each patient was studied to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
0
22
3
Order By: Relevance
“…Older age has been shown to be associated with increased risk of both DES and dementia [1]. Previous studies demonstrated that patients with dementia have a greater risk of developing dry eye and Sjögren's syndrome [21,22]. However, we found a decreased risk of DES in dementia patients in our multivariate models.…”
Section: Discussioncontrasting
confidence: 71%
“…Older age has been shown to be associated with increased risk of both DES and dementia [1]. Previous studies demonstrated that patients with dementia have a greater risk of developing dry eye and Sjögren's syndrome [21,22]. However, we found a decreased risk of DES in dementia patients in our multivariate models.…”
Section: Discussioncontrasting
confidence: 71%
“…Previous studies demonstrated that patients with dementia have a greater risk of developing dry eye and Sjögren's syndrome (* 18,19). However, we found a decreased risk of DES in dementia patients in our multivariate models.…”
Section: Discussioncontrasting
confidence: 72%
“…Furthermore, patients with DES had significantly greater risks of schizophrenia (OR = 1.34), bipolar disease (OR = 1.90), depression (OR = 1.54), sleeping disturbance/ insomnia (OR =1. 19), and neurotic disorders (OR = 1.24), including anxiety (OR = 1.34), than those without DES. However, prevalence of DES was significantly lower in patients with dementia (OR = Our study also found that anxiety disorder was correlated with DES, which supports the findings of two previously reported case-control studies (*4,18).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, patients with DES had significantly greater risks of schizophrenia (OR = 1.34), bipolar disease (OR = 1.90), depression (OR = 1.54), sleeping disturbance/ insomnia (OR =1. 19), and neurotic disorders (OR = 1.24), including anxiety (OR = 1.34), than those without DES. However, prevalence of DES was significantly lower in patients with dementia (OR = 0.73) and mental retardation (OR = 0.25).…”
Section: Discussionmentioning
confidence: 95%